2012
DOI: 10.2174/092986712802002572
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-Related Factors and Oxidative Stress in Autism, A Review

Abstract: Autism spectrum disorders are complex neuro-developmental disorders whose neurobiology is proposed to be associated with oxidative stress which is induced by reactive oxygen species. The process of oxidative stress can be a target for therapeutic interventions. In this study, we aimed to review the role of oxidative stress, plasma glutathione (GSH), and related factors as the potential sources of damage to the brain as well as the possible related factors which reduce the oxidative stress. Methylation capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 79 publications
4
66
0
6
Order By: Relevance
“…A previous review article suggested that declining ROS levels are coupled with increased antioxidant enzyme activities, depending on the formation of antioxidant enzymes relative to the changes in the levels of free radicals [54]. Moreover, growing evidence indicates that the imbalance between ROS production and TAC may correlate with ASD [55,56]. Thus, the present study first revealed detailed and concrete findings on the imbalance between oxidative stress and TAC in the urine of individuals with ASD.…”
Section: Predictor Variablesmentioning
confidence: 55%
See 1 more Smart Citation
“…A previous review article suggested that declining ROS levels are coupled with increased antioxidant enzyme activities, depending on the formation of antioxidant enzymes relative to the changes in the levels of free radicals [54]. Moreover, growing evidence indicates that the imbalance between ROS production and TAC may correlate with ASD [55,56]. Thus, the present study first revealed detailed and concrete findings on the imbalance between oxidative stress and TAC in the urine of individuals with ASD.…”
Section: Predictor Variablesmentioning
confidence: 55%
“…Previous studies examined urinary oxidative stress biomarkers such as F2-isoprostanes and their association with the activity of plasma enzymatic antioxidants such as SOD and glutathione peroxidase [83,84]. In this study, the urinary levels of 2-isoprostanes and plasma levels of glutathione were not measured; however, we examined a useful and informative set of oxidative stressrelated biomarkers and discovered novel important information on impaired antioxidant capacity that was not revealed in previous studies [6,11,25,85]. Second, ASD is most prevalent in males, with a male to female ratio of 4 to 1 [86].…”
Section: Predictor Variablesmentioning
confidence: 93%
“…Markers of inflammation, mitochondrial and immune dysfunction, and altered metabolism of homocysteine and methionine, all evidence of oxidant stress, have also been associated with autism. 5,6 We have reported that p75NTR is a cytoplasmic antioxidant and mitochondrial oxidant in neural crest cell lines. 9, 10, 11 We have defined its antioxidant signaling pathway to involve neurotrophin binding to p75NTR; upregulation of the cholesterol biosynthetic pathway; palmitoylation of p75NTR; phosphorylation of p75NTR; cleavage of p75NTR by α- and γ-secretase to its intracellular fragment, p75ICD; translocation of p75ICD to the nucleus; and phosphorylation of Akt.…”
Section: Discussionmentioning
confidence: 98%
“…1 Aberrancy of cerebellar Purkinje cell connectivity, expression of brain-derived neurotrophic factor (BDNF) and handling of inflammation and oxidative stress have been implicated in the manifestations of autism. 3, 4, 5, 6 Candidate molecules for involvement in the pathogenesis of autism should best demonstrate developmental regulation and relevance to these processes and functions.…”
Section: Introductionmentioning
confidence: 99%
“…The recycled twooxygen particle O -2 O 2 nano bubble works as an activated gas nucleus, engulfing close oxygen particles. The increase in the surrounding pressure (see δP' arrow) is expected to enhance the oxygen nanobubble nucleation, resulting in an increased NADPH oxidase activity(= increased superoxide) and an increased bubble scavenging (NO synthase induction, increased SOD activity and iron bioavailability, hence increased ROS).To summarize, and as depicted in the diagram, the antibubble bio machinery scavenges oxygen overload arising from oxygen nano bubbles after a 3-stage enzymatic pathway: nano bubble fission, implosion and scavenging [4]. In certain conditions, such as SOD activity or depending on iron bioavailability, oxygen quantum bubbles could be recycled.…”
mentioning
confidence: 99%